Paulo Freire para crianças - Silva, Rafaela Pastore Oliveira da [UNESP] (2010)
The experiences lived in the Read and Write Program (Programa Ler e Escrever), through the scholarship project Public School and University at literacy (Escola Pública e Universidade na alfabetização), were the starting point for the preparation of this research. From this observations obtained in the classroom, it was noticed gaps present in the process of teaching-learning in the system imposed by the state government of Sao Paulo, preponderant factors to understand how and when children learn. This way, was noted that only one literacy proposal to be adopted by all schools revealed not being efective to meet different contexts, also disregards the individuality of each student. Thus, we applied the Paulo Freire's Method with children from Second year (Former First series) adapted in a playful way, during reinforcement classes at state shcool “Torquato Minhoto”, located in Bauru/SP. Sought to promote, properly, the comprehension of the language code and the development of learning in reading and writing. This manner, some barriers prevented a more thorough job covering a wider range of studantes over an extended period, however, the results were generally positives about the startup of literacy